2021
DOI: 10.1007/s00170-021-07750-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the hole quality produced by vibratory drilling: additive manufactured PLA+

Abstract: Improving the surface quality of additive manufactured parts like poly lactic acid (+) is an important study that is currently being carried out by researchers. To reach the high quality, different conventional and non-conventional methods are applied. In this study, the capability of ultrasonic vibration in drilling of an additive manufactured poly lactic acid (+)was examined. The process was implemented in two methods: conventional and vibratory drilling.Then, thrust force and chip type were analyzed and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…The comparison was carried out in terms of the delamination factor, the cylindricity of the delaminated areas, and the circularity of the drilled holes; consequently, it was suggested that the feed rate value has a kind of directly proportional relationship with the delamination factor, while increasing the cutting speed affected such proportionality. This observation contrasts with the results obtained in a previous study on polylactic acid (PLA) drilling, where cutting speed did not appear to have a significant effect on the delamination factor [59]. It may be suggested that the presence of natural fibers produced this effect, which was likely due to the nonuniformity of their local properties, suggesting that limiting the time that the material is in contact with the tool via increasing the drilling speed might also reduce the extent of the damage.…”
Section: Main Parameters Influencing Drilling Of Natural Fiber Compos...contrasting
confidence: 99%
“…The comparison was carried out in terms of the delamination factor, the cylindricity of the delaminated areas, and the circularity of the drilled holes; consequently, it was suggested that the feed rate value has a kind of directly proportional relationship with the delamination factor, while increasing the cutting speed affected such proportionality. This observation contrasts with the results obtained in a previous study on polylactic acid (PLA) drilling, where cutting speed did not appear to have a significant effect on the delamination factor [59]. It may be suggested that the presence of natural fibers produced this effect, which was likely due to the nonuniformity of their local properties, suggesting that limiting the time that the material is in contact with the tool via increasing the drilling speed might also reduce the extent of the damage.…”
Section: Main Parameters Influencing Drilling Of Natural Fiber Compos...contrasting
confidence: 99%
“…The material properties, specific print parameters inherent to each material, as well as the achieved sample sizes, are characterised in Table I. This study employs the most common thermoplastic materials used in FDM, namely: (i) ABS (acrylonitrile butadiene styrene), characterised by its high impact and heat resistance [15]; (ii) PLA (polylactic acid), for its ease of printing [16] and low shrinkage, achieving the closest dimensions compared to the intended ones in Table I; (iii) PLA+, an enhanced version of PLA with increased strength to weight qualities [17]; and (iv) PETG (Polyethylene terephthalate glycol), a co-polymer combining the best features of PLA (low shrinkage) and ABS (high impact resistance) [18].…”
Section: Methodology a Materials And Manufacturingmentioning
confidence: 99%
“…Using AM also called 3D printing, is rising because of the process flexibility and ability to produce complex structures in less time. 1,2 One of the common methods in AM is Fused Deposition Modeling (FDM). FDM was introduced in the 1990s by Stratasys Inc. 3 FDM is a 3D printing process that continuous filament or thermoplastic material is fed by a moving and heated nozzle (print extruder head) and deposited on a growing part.…”
Section: Introductionmentioning
confidence: 99%